2020
DOI: 10.1101/2020.07.15.20153791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physical activity, mental health and well-being of adults during early COVID-19 containment strategies: A multi-country cross-sectional analysis

Abstract: Objectives: To assess how the early stages of National governments Coronavirus disease (COVID-19) containment strategies impacted upon the physical activity, mental health and well-being of adults in the UK, Ireland, New Zealand and Australia Design: Observational, cross-sectional Setting: Online survey disseminated in the UK, Ireland, New Zealand and Australia within the first 2-6 weeks of government mandated COVID-19 restrictions Participants: Adults (n = 8,425; 44.5 [14.8] y), ≥ 18 y who were residing in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 18 publications
(30 reference statements)
4
20
1
Order By: Relevance
“…In our survey, those respondents who continued to maintain their usual level of physical activity throughout the lockdown, recognized the importance of PA on their well-being especially mental health. This is in line with other research that has shown the benefits of physical activity on mental health [ 18 , 43 , 44 , 45 ] and in particular with a survey conducted in New Zealand that showed positive correlations between self-reported PA and well-being [ 43 ]. In this study, people who had negative or no change in their PA from pre-during lockdown, reported worse well-being, depression, stress and anxiety compared to those who had positive changes in PA [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our survey, those respondents who continued to maintain their usual level of physical activity throughout the lockdown, recognized the importance of PA on their well-being especially mental health. This is in line with other research that has shown the benefits of physical activity on mental health [ 18 , 43 , 44 , 45 ] and in particular with a survey conducted in New Zealand that showed positive correlations between self-reported PA and well-being [ 43 ]. In this study, people who had negative or no change in their PA from pre-during lockdown, reported worse well-being, depression, stress and anxiety compared to those who had positive changes in PA [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Respondents in our survey would be considered as being sufficiently physically active according to the current World Health Organisation (WHO) physical activity guidelines for adults [ 42 ]. In a similar survey conducted in four high-income countries including New Zealand, it was found that adults in New Zealand had the least change to their physical activity in the early stages of the lockdown [ 43 ]. In New Zealand the movement restrictions still allowed for engagement in exercise in the vicinity of people’s homes therefore this may have also contributed to allowing people to continue with some physical activity during lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed negative impacts of the lockdown on mental health and physical activity [ 47 , 48 , 49 ]. Some researchers investigated pandemic-related stages of change in exercise behavior based on the transtheoretical model of behavior change [ 50 ], and participants who were at a negative stage of change during the early COVID-19 restrictions showed poorer mental health and well-being than did participants in other change stages [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research as to how COVID-19-associated restrictions influenced general physical activity levels is somewhat equivocal, with some studies indicating an increase in overall participation [15][16][17] and others showing a negative impact [18,19]. Variances appear to be explained, at least in part, by region-specific and both demographic and socio-economic factors [19,20]. However, while these studies provide insights into general global physical activity patterns, there is little research into how the pandemic influenced RT behaviours.…”
mentioning
confidence: 99%
“…However, while these studies provide insights into general global physical activity patterns, there is little research into how the pandemic influenced RT behaviours. While one report suggested that women and younger ages groups may have reduced engagement in RT [20], others have reported RT as being a more common form of exercise during-the lockdown [18]. With the closure of the typical locations for engaging in RT, many have offered recommendations to adapt and continue engagement in 'muscle strengthening activity' such as RT at home, and with alternative modalities (such as bodyweight exercise or home equipment), both for the general population [21][22][23][24][25], and for sports participants [26][27][28].…”
mentioning
confidence: 99%